Origin of Difference in Photocatalytic Activity of ZnO (002) Grown on a- and c-Face Sapphire - Guoqiang Li; Bingyang Sun; Yali Wang; Zhou Wu; Weifeng Zhang (International Journal of Photoenergy)
The oriented (002) ZnO films were grown on a- and c-face sapphire by pulsed laser deposition. The X-ray diffraction analysis revealed that the oriented (002) ZnO films were epitaxially grown on the substrate successfully. The sample on a-face sapphire had higher crystal quality. However, the photocatalytic activity for Rhodamine B degradation of ZnO film on c-face sapphire was higher than that on a-face sapphire. The Raman spectrum and XPS analysis suggested that the sample on a-face sapphire had higher concentration of defects. The result of the contact angle measurement revealed that the sample on c-face sapphire had higher surface energy. And the investigation of the surface conductance implied that the higher light conductance was helpful for the photocatalytic activity.